Faktor-faktor yang Mempengaruhi Keputusan Konsumen Dalam Pembelian Sayuran Organik di Pasar Modern Kota Denpasar - DARMAWATI, MADE CINDY; DARMAWAN, DWI PUTRA; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Factors Influence Consumers Decisions in Purchasing Organic Vegetables  in the Modern Market of Denpasar City Organic vegetables are one of the products produced from agriculture that are environmentally friendly and closer to the concept of nature, so that it can provide a guarantee of good quality compared to ordinary vegetables. The purpose of this study was to determine the factors that influence consumers decisions in purchasing organic vegetables and the most dominant factors influencing consumers decisions in purchasing organic vegetables in the Modern Market of Denpasar City. The data in this study consisted of qualitative data and quantitative data obtained from primary data sources and secondary data. The sampling technique was done by accidental sampling and obtained 50 respondents. The analysis technique used is SEM-PLS. The dependent variable (Y) is the consumers decisions and the independent variable (X) is price, product quality, location, service, and attitude. The results showed that the variables of price, product quality, and service had a significant effect, while the variables of location and attitude had no significant effect. The dominant variable that influences consumers decisions in purchasing organic vegetables in the Denpasar Modern Market is the price variable. Suggestions for this research are expected in the Modern Market can pay attention to the prices offered. Affordable prices supported by friendly service and appropriate product quality. The location is expected to be easy to reach and the attitude is well received.